Addressing the Antibiotic Resistance Problem with Probiotics: Reducing the Risk of Its Double-Edged Sword Effect - Imperial, Ivan C. V. J.; Ibana, Joyce A. (Frontiers in Microbiology, 2016)
Antibiotic resistance is a global public health problem that requires our attention. Indiscriminate antibiotic use is a major contributor in the introduction of selective pressures in our natural environments that have significantly contributed in the rapid emergence of antibiotic-resistant microbial strains. The use of probiotics in lieu of antibiotic therapy to address certain health conditions in both animals and humans may alleviate these antibiotic-mediated selective pressures. Probiotic use is defined as the actual application of live beneficial microbes to obtain a desired outcome by preventing diseased state or improving general health. Multiple studies have confirmed the beneficial effects of probiotic use in the health of both livestock and humans. As such, probiotics consumption is gaining popularity worldwide. However, concerns have been raised in the use of some probiotics strains that carry antibiotic resistance genes themselves, as they have the potential to pass the antibiotic resistance genes to pathogenic bacteria through horizontal gene transfer. Therefore, with the current public health concern on antibiotic resistance globally, in this review, we underscore the need to screen probiotic strains that are used in both livestock and human applications to assure their safety and mitigate their potential in significantly contributing to the spread of antibiotic resistance genes in our natural environments.